Exploring the predictors and prognostic significance of exercise-induced cardiac troponin release in master athletes following a 28 km mountain race. The Vamvakou research project - Stavroulakis, G.; Methenitis, S; Koutroulis,G.; Xanthis, D.; Cherouveim,E.; Kroupis, C.; Anastasiadis, G.; Ketselidi,K.; Vlachopoulou,E.; Tsolakis, C.; Koulouvaris,P. (Biomarkers, 2022)
BACKGROUND/OBJECTIVE: Aetiology and significance of exercise-induced troponin release remains a contentious issue. We investigated the effect of a 28 km mountain run on cardiac troponin I (cTnI), in relation to training, performance, nutritional, biochemical and echocardiography variables, in a group of 25 recreational male master athletes. MATERIAL AND METHODS: A comprehensive list of variables related with nutrition, training, performance and echocardiography, was collected pre- and post-race. Twenty-four months later, outcomes regarding cardiovascular events were obtained. RESULTS: Serum cTnI values were increased after the race, with mean values rising from 7.2 +/- 2.2 (before) to 80.0 +/- 33.2 ng/L (post race), (p < 0.001) and 23/25(92%) exceeding Upper Reference limit (50 ng/L). Echocardiography did not reveal significant alterations, or correlations with cTnI values. The percentage difference in hs-cTnI concentrations pre- and post-race correlated positively with age, race-induced changes of selected muscle damage indices, resistance training volume and negatively with endurance capacity and training volume (r: -0.727 to 0.725, p < 0.05). All athletes reported no cardiovascular event during the 24-month period post-race. CONCLUSION: cTnI elevation induced by a 28 km mountain running race was not correlated with echocardiographic, nutritional parameters and was less pronounced in athletes with larger endurance training history, in contrast with resistance training and age
IS - 1366-5804 (Electronic) IS - 1354-750X (Linking) LA - eng PT - Journal Article RN - 0 (Biomarkers) RN - 0 (Troponin I) SB - IM
Keywords: Athletes; Biomarkers; Echocardiography; Humans; Male; Physical Endurance; physiology; Prognosis; Running; Troponin I